An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

Thermo-hydraulic Performance of Pillow-Plate Heat Exchangers with Secondary Structuring: A Numerical Analysis - Afsahnoudeh, Reza; Wortmeier, Andreas; Holzmüller, Maik; XGong, Yi; Homberg, Werner; Kenig, Eugeny Y. (Energies)

Sure you are ready? Gendered arguments in recruitment for high-status positions in male-dominated fields - Dutz, Regina; Hubner-Benz, Sylvia; Emmerling, Franziska; Peus, Claudia (Frontiers in Psychology)
Recruitment contexts such as STEM professorships promote clearly defined selection criteria and objective assessment. We illuminate in these contexts, the subjective interpretation of seemingly objective criteria and gendered arguments in discussions of applicants. Additionally, we explore gender bias despite comparable applicant profiles investigating how specific success factors lead to selection recommendations for male and female applicants. Implementing a mixed methods approach, we aim to highlight the influence of heuristics, stereotyping, and signaling in applicant assessments. We interviewed 45 STEM professors. They answered qualitative open-ended interview questions, and evaluated hypothetical applicant profiles, qualitatively and quantitatively. The applicant profiles enabled a conjoint experiment with different applicant attributes varied across the profiles (i.e., publications, willingness to cooperate, network recommendation, and applicant gender), the interviewees indicating scores of selection recommendation while thinking aloud. Our findings reveal gendered arguments, i.e., questioning women potentially fueled by a perception of women’s exceptional status and perceived self-questioning of women. Furthermore, they point to gender-independent and gender-dependent success patterns, thereby to potential success factors particularly for female applicants. We contextualize and interpret our quantitative findings in light of professors’ qualitative statements.
Keywords: General Psychology

Robot leadership–Investigating human perceptions and reactions towards social robots showing leadership behaviors - Cichor, Jakub Edward; Hubner-Benz, Sylvia; Benz, Tobias; Emmerling, Franziska; Peus, Claudia (PLOS ONE)
Human-robot interaction research has shown that social robots can interact with humans in complex social situations and display leadership-related behaviors. Therefore, social robots could be able to take on leadership roles. The aim of our study was to investigate human followers’ perceptions and reactions towards robot leadership behavior, and differences based on the robot’s displayed leadership style. We implemented a robot to show either a transformational or a transactional leadership style in its speech and its movements. We presented the robot to university and executive MBA students (N = 29) and subsequently conducted semi-structured interviews and group discussions. The results of explorative coding indicated that participants differed in their perceptions and reactions based on the robot’s leadership style and based on their assumptions about robots in general. We observed that participants quickly imagined either a utopia or worried about a dystopia, depending on the robot’s leadership style and their assumptions, and that a subsequent reflection led to more nuanced views. We discuss the implications and recommendations for human-robot interaction and leadership research.
Keywords: Multidisciplinary

What predicts effectuation preferences Disentangling individual and environmental factors and illuminating decision criteria - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Different ways lead to ambidexterity: Configurations for team innovation across China, India, and Singapore - Deng, Wei; Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli (Journal of International Management)
Keywords: Strategy and Management; Finance; Business and International Management

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Combined Economic and Emission Dispatch of a Microgrid Considering Multiple Generators - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand side management potential of refrigeration appliances - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 2023 IEEE PES/IAS PowerAfrica Conference)

Demand-Side-Management for Optimal dispatch of an Isolated Solar Microgrid - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Proceedings of the 2023 IEEE AFRICON, Nairobi, Kenya)

Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert

Igor Levit - No Fear! Ein Film von Regina Schilling - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik (https://www.theomag.de/145/hsw24.pdf))

A Methodical Approach to Hybrid Modelling for Contextual Anomaly Detection on Time-Series Data - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Innovative self-learning disturbance compensation for straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Materials Research Proceedings)
Abstract. To increase the sustainability of forming processes such as punch bending, homogenization of the processed semi-finished product is an essential step in the manufacturing process. High-strength wire materials are usually available as strip material before being further processed in a forming process. For storage and transport, the material is coiled onto coils and transported to the customer. During the coiling process, residual stresses and plastic deformation are introduced into the wire. Thus, the final product quality is also influenced by the geometry of the coil. Straightening machines are used in production lines to compensate for these. Once a straightening machine has been set up, the settings for the roll positions are usually not changed. As a result, there is no reaction to material fluctuations, which means that the components to be produced do not meet the dimensional accuracy requirements. This leads to an increase in the rejection rate in manufacturing processes. To reduce the rejection rate, it is necessary to enable dynamic and flexible infeed of the straightening rollers. In this context, an innovative control concept with disturbance compensation was developed for the straightening process. The disturbance compensation uses a disturbance model that predicts the change in bending curvature over the coil radius. With this prediction, the straightening machine can be adjusted specifically. The roller positions are adjusted by a subordinate position control. The additional feedback from measured geometric product properties from the following punching-bending process enables the straightening machine to be adjusted even in the case of unforeseen fluctuations in the material properties. In this way, it is possible to react to any material fluctuations as required. This novel, demand-oriented adjustment of the straightening machine is expected to result in a high increase in the efficiency of the production process and a reduction of the rejection rate.

Neuartiger Ansatz zum Richten von zwei- und dreidimensionalen Fehlern an einem Federdraht - Bathelt, Lukas; Djakow, Eugen; Dahms, Frederik; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Ilmenauer Federntag 2023: Neueste Erkenntnisse zu Funktion, Berechnung, Prüfung und Gestaltung von Federn und Werkstoffen)

Learning the Automated Setup of Profile Wrapping Lines for New Products from Few Past Setups - Koppert, Steven; Bause, Maximilian; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Lithium niobate waveguide squeezer with integrated cavity length stabilisation for network applications - Stefszky, M.; vom Bruch, F.; Santandrea, M.; Ricken, R.; Quiring, V.; Eigner, C.; Herrmann, H; Silberhorn, C (Optics Express)
We report a titanium indiffused waveguide resonator featuring an integrated electro-optic modulator for cavity length stabilisation that produces close to 5 dB of squeezed light at 1550 nm (2.4 dB directly measured). The resonator is locked on resonance for tens of minutes with 70 mW of SH light incident on the cavity, demonstrating that photorefraction can be mitigated. Squeezed light production concurrent with cavity length stabilisation utilising the integrated EOM is demonstrated. The device demonstrates the suitability of this platform for squeezed light generation in network applications, where stabilisation to the reference field is typically necessary.
Keywords: Atomic and Molecular Physics; and Optics

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Analysis and Optimization of Joint Formation in Hybrid Compression Molding - Lückenkötter, Julian; Aydin, Simon; Marten, Thorsten; Tröster, Thomas

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Wer übernimmt Verantwortung für Inklusion? - Kottmann, Brigitte; Lütje-Klose, Birgit; Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Bildungspolitik; Schulentwicklung; Sonderpädagogik

Elektrooptischer Balun und System zur Generierung eines pseudodifferentiellen Signals aufweisend einen solchen elektrooptischen Balun - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Balun, wobei der elektrooptische Balun einen Eingang für ein optisches Eingangssignal (Ein(t)) aufweist, wobei der elektrooptische Balun weiterhin ein 1x2 Multimodeninterferometer (1x2 MMI) und einen Phasenschieber (Δϕ) aufweist, wobei das 1x2 Multimodeninterferometer (1x2 MMI) mit dem Eingangssignal im Betrieb versorgbar ist, wobei der elektrooptische Balun weiterhin ein 2x4 Multimodeninterferometer (2x4 MMI) aufweist, wobei das 2x4 Multimodeninterferometer (2x4 MMI) mit den Ausgangsarmen des 1x2 Multimodeninterferometer (1x2 MMI) verbunden ist, wobei der Phasenschieber (Δϕ) in einem Ausgangsarm des 1x2 Multimodeninterferometer (1x2 MMI) angeordnet ist, wobei im Betrieb an zwei Ausgängen (Eout,1 (t), Eout,4(t)) des 2x4 Multimodeninterferometers (2x4 MMI) ein quasi differentielles optisches Signal anliegt, das mittels einer jeweiligen Photodiode (PD1, PD2) und einem differentiellen Schaltkreis in ein DC-freies elektrisches Signal (Vout) überführt werden kann. Weiterhin betrifft die Erfindung ein System zur Generierung eines pseudeodifferentiellen Signals, aufweisend einen elektrooptischen Balun sowie einen optischen Strahlteiler (OS) sowie einen dual output carrier injection Mach Zehnder Modulator (MZM), wobei der optische Strahlteiler (OS) ein Eingangssignal (IIN) in einen ersten Teil (n) und einen zweiten Teil (1-n) aufteilt, wobei der zweite Teil (1-n) als Eingangssignal (Ein(t)) im Betrieb auf den Eingang des elektrooptischen Baluns geführt wird, wobei der erste Teil (n) im Betrieb als Eingangssignal dem dual output carrier injection Mach Zehnder Modulator (MZM) zugeführt wird, wobei das quasi differentielle elektrische Signal (I1, I2) der Photodioden (PD1, PD2) im Betrieb zur Ansteuerung des dual output carrier injection Mach Zehnder Modulator (MZM) in push pull Konfiguration verwendet wird.

Elektrooptischer Mischer - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Mischer (1) mit elektrischem Ausgang, aufweisend: • eine Photodiode (PD), • einen ersten Anschluss, • einen zweiten Anschluss, • wobei die Anschlüsse eine erste Spannungsversorgung (V1) und eine zweite Spannungsversorgung (V2) oder eine erste Stromversorgung (I1) und eine zweite Stromversorgung (I2) anschließbar ist, • einen Anschluss für ein Kleinsignal-Massepotential, • ein erstes Teilanpassungsnetzwerk (Z2, Z4), welches auf der Anodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des ersten Teilanpassungsnetzwerkes (Z2) mit dem Anschluss für die zweite Spannungsversorgung (V2) schaltbar (S2) verbindbar ist, und wobei ein anderer Teil des ersten Teilanpassungsnetzwerkes (Z4) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S2') verbindbar ist, • ein zweites Teilanpassungsnetzwerk (Z1, Z3), welches auf der Kathodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des zweiten Teilanpassungsnetzwerkes (Z1) mit dem Anschluss für die erste Spannungsversorgung (V1) schaltbar (S1) verbindbar ist, und wobei ein anderer Teil des zweiten Teilanpassungsnetzwerkes (Z3) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S1') verbindbar ist, • ein erstes entkoppelndes Element (C1) angeordnet auf der Kathodenseite und ein zweites entkoppelndes Element (C2) angeordnet auf der Anodenseite der Photodiode (PD), • wobei zwischen den von der Photodiode (PD) abgewandten Seiten des ersten entkoppelnden Elementes (C1) und des zweiten entkoppelnden Elementes (C2) im Betrieb einelektrisches Ausgangssignal bereitgestellt werden kann.

ENHANCED PLL CIRCUIT - Iftekhar, Mohammed; Scheytt, J. Christoph

Photonic Quantum Enhanced Radar Systems - Kruse, Stephan

Einfluss von Infrarotschweißprozessparametern auf die quasistatische und zyklische Belastbarkeit von technischen glasfaserverstärkten Thermoplasten - Gevers, Karina; Töws, P.; Schraa, L.; Decker, J.; Schöppner, Volker; Uhlig, K.; Stommel, M. (11. Landshuter Leichtbau-Colloquium)

A NEW APPROACH FOR THE LOCAL DETERMINATION OF ENERGY INPUT IN CO-ROTATING TWIN SCREW EXTRUDERS BASED ON SCREW TORSION - Schöppner, Volker; Austermeier, Laura; Nordieker, A.

Development Of An Asymmetric Torque Model For The Two Screws Of A Twin Screw Extruder - Schöppner, Volker; Austermeier, Laura; Alsoud, A.

Auswirkungen unterschiedlicher Erwärmstrategien auf infraroterwärmte Polyphthalamide - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J. (Joining Plastics)

Devulkanisation schwefelvernetzender Elastomere im halbleitergestützten Mikrowellenverfahren - Schöppner, Volker; Petzke, J.

Numerical investigations of new low‐order explicit last stage diagonal implicit Runge–Kutta schemes with the finite‐element method - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Abstract Initial value problems can be solved efficiently by means of Runge–Kutta algorithms with adaptive step size control. Diagonally implicit Runge–Kutta (DIRK) methods are the most popular class among the diverse family of Runge–Kutta algorithms. In this paper, the novel class of low‐order explicit last‐stage diagonally implicit Runge–Kutta (ELDIRK) methods are explored, which combine implicit schemes with an additional explicit evaluation as an explicit last stage. ELDIRK Butcher tableaus are used to control embedded RK methods to obtain solutions of different orders. The lower‐order solution is obtained by classical implicit RK stages and the higher‐order solution is obtained by additional explicit evaluation. As a result, a significant reduction in computational cost is achieved by skipping the iterative solution of nonlinear systems for the additional step. The examination of the heat problem and the use of the innovative Butcher tableau in the finite‐element method are the main contributions of this work. Thus, it is possible to establish adaptive step size control for the new low‐order embedded methods based on an empirical method for error estimation. Two‐dimensional simulations are used to show an appropriate algorithm for the ELDIRK schemes. The new Runge–Kutta schemes' predictions of higher‐order convergence are confirmed, and their successful outcomes are illustrated.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

No effects of different perturbations on the performance in a mental body-rotation task (MBRT) with egocentric perspective transformations and object-based transformations - Budde, Kirsten; Weigelt, Matthias (Human Movement Science)
The present study investigates participants' performance in two different mental body-rotation tasks (MBRTs) under conditions in which dynamic stability is challenged in two different balancing conditions: active balance control (Experiment 1), where participants actively maneuver, and re-active balance control (Experiment 2), where participants react to an external perturbation. The two MBRTs induced either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment). In Experiment 1, 48 participants were tested while standing on an even ground (low balancing requirements) or on a balance board (high balancing requirements). In Experiment 2, 32 participants performed while either standing still on a vibration plate or with the vibration plate moving in a low (20 Hz) or high (180 Hz) frequency. In both experiments, the results for response time and response error revealed effects of rotation angle and type of task. An effect of balancing condition was only observed for response error in Experiment 1. More precisely, response times and response errors increased for higher rotation angles. Also, performance was better for egocentric than for object-based spatial transformations. However, the different challenges to dynamic stability in Experiments 1 and 2 did not influence performance in the two MBRTs (except for response errors in Experiment 1) nor in a control condition (Experiment 1) without mental rotation.
Keywords: Mental rotation; Balance control; Perturbation; Embodiment

Rezension: Erika Thomalla: Anwälte des Autors. Zur Geschichte der Herausgeberschaft im 18. und 19. Jahrhundert, Göttingen: Wallstein 2020 und Ines Barner: Von anderer Hand. Praktiken des Schreibens zwischen Autor und Lektor, Göttingen: Wallstein 2021 - Spener, Anna Maria; Heimgartner, Stephanie (Sprache und Literatur)

Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Methoden zur Förderung von Kompetenzen für eine demokratische Kultur - Schriftliche Reflexionen von Lehramtsstudierenden aus bildungswissenschaftlichen Seminaren - Wehde, Janis; Bloh, Bea

Wie war das damals? Oral history und Zeitzeug:innenbefragung - Diederich, Julia ((Über-)Leben im Nationalsozialismus)